Biochemical sensors : Mimicking gustatory and olfactory senses - Toko, Kiyoshi (Singapore : Pan Stanford, 2013)
This book is the first to comprehensively treat sensors for gustatory and olfactory senses. It will be highly useful to students and researchers in a wide variety of scientific fields and also to those in the fields of foods, perfumes, medicines and robotics as the sensor applications.
Index 531-560p.
Keywords: Herbal medicines; Order recorder; Bitterness medicines